Penentuan Sifat Fisikokimia Madu Hutan (Apis dorsata) Sulawesi Selatan - Sjamsiah, Sjamsiah; Sikanna, Rismawati; Rifkah.A, Azmalaeni; Saleh, Asri (Al-Kimia, 2018)
The physicochemical propertis of forest honey (Apis dorsata) become one of the supporting qualities of honey. Good honey can be viewed from the quality of honey which refers to the Indonesian National Standard (SNI). Therefore, this research aims to determine the physicochemical properties of forest honey from the village of Bonto Manurung, Maros district, Tompobulu village, Pangkep district and Paranglompoa village, Gowa district in accordance with the SNI. The results showed that the best physicochemical properties of honey were from the village of Bonto Manurung, Gowa district which had a moisture content of 19.19 %b/b, ash content of 0.045 %b/b, viscosity of 14.82 poise , acidity is 42.43 mL N NaOH/kg, reducing sugar is 69 %b/b and HMF levels are 2.99 mg/kg. As for the analysis of metallic impurities, all samples examined forest honey is not contaminated by metals arsenic (As), cadmium (Cd) and lead (Pb).